Joint Deformities in Patients of Rheumatoid Arthritis Report of 112 cases from Lahore, Pakistan (Journal of Fatima Jinnah Medical University, 2018)
Background : Rheumatoid arthritis is a chronic systemic inflammatory autoimmune disease typically involving joints causing symmetric polyarthritis leading to progressive joint destruction and functional impairment .Objectives: To determine the frequency and pattern of joint deformities in patients with rheumatoid arthritis.Study Design: Descriptive case series.Place and duration of study: Department of Medicine Shaikh Zayed Medical Institute, Lahore from 01- 01- 13 to 30-06-13.Subjects and Methods: Hundred and twelve patients with rheumatoid arthritis of both sexes above fifteen years of age fulfilling the ACR 2010 criteria were evaluated for age, gender and pattern of joint involvement.Results: There were 13 (11.68%) males and 99 (88.4%) female patients, male to female ratio was 1:7.6. 13.4% of the patients were below and 86.6% of the patients were above 30 years of age. Mean age of the patients was 42.38 ±10.7 years. Thirty-nine patients (34.8%) presented with various joint deformities. Small joints of hands were most commonly involved.Conclusion: The joint involvement in rheumatoid arthritis is quite extensive. The disease should be diagnosed at an early stage for proper management and to prevent complications.
Keywords: Rheumatoid arthritis, joint deformity.